Upaya meningkatkan Kemampuan Pemecahan Masalah melalui Model Problem Posing pada Mata Pelajaran Matematika - Hendhisca Cipta; Tria Lestari (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
This research is motivated by the low problem solving ability of students in Mathematics in class V SDIT Nurut Taqwa West Cikarang. This study aims to improve the ability to solve Mathematical problems through Problem Posing learning models for fifth grade students at SDIT Nurut Taqwa Cikarang Barat. This research method uses Classroom Action Research (CAR) which consists of 3 cycles. Each cycle consists of stages of action planning, implementation of actions, stages of observation and assessment, then reflection. Subjects numbered 19 students. The data in this collection was obtained using data collection techniques in the form of written tests and observations. The criterion for success in this study is if 80% of the number of students reach the KKM value that has been set is 70. Based on the results of the study obtained in cycle I, the problem solving ability of students obtained a percentage of mastery learning by 32% with an average value of 58.95. In cycle II, the problem solving ability of students obtained a percentage of completeness of 63% with an average value of 74. In cycle III, the problem solving ability of students obtained a percentage of mastery learning by 89% with an average value of 85. The conclusion of this study is a model Problem Posing learning can improve Mathematical problem solving skills in fifth grade students at SDIT Nurut Taqwa Cikarang Barat.